Penyuluhan Tentang Pengelolaan Sampah Organik dan Anorganik Hasil Praktek di SMK Swasta Nurul Amaliyah - Saputra, Andi; Napitupulu, Abidan; Siburian, Mananda Ture (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Waste management is a crucial issue in maintaining environmental sustainability, especially in an educational environment that produces significant amounts of organic and inorganic waste. This study aims to evaluate the effectiveness of the counseling program on waste management at Nurul Amaliyah Private Vocational School and provide recommendations for a more sustainable system. The method used is a qualitative descriptive approach with observation, interview, and questionnaire techniques involving students, educators, and cleaning staff. The results of the study showed that after participating in counseling, students' understanding of waste classification and processing increased significantly. However, the main obstacles faced in the implementation of the waste management system are the lack of supporting facilities, such as adequate sorted waste bins and the absence of an integrated compost-based waste management system. As a solution, it is recommended that schools implement a sustainable approach by providing better waste management facilities, conducting periodic training, and collaborating with external parties in supporting recycling programs. In addition, strengthening the environment-based curriculum can also be an effective strategy in instilling ecological awareness in students from an early age.